The nature of the Moho beneath fast‐spreading centers: Evidence from the Pacific plate and Oman ophiolite. (21st September 2022) - Tamura, Yoshihiko; Rospabé, Mathieu; Fujie, Gou; Ohira, Akane; Kaneda, Kentaro; Nichols, Alexander R. L.; Ceuleneer, Georges; Sato, Tomoki; Kodaira, Shuichi; Miura, Seiichi; Takazawa, Eiichi
Abstract: It is common knowledge that the Moho is the boundary between the crust and the Earth's mantle. Here we show along several seismic profiles through the Pacific Plate that a correlation exists between the strength of Moho reflections, crustal thickness, and water depth. Where the Moho can be detected clearly, the overlying oceanic crust is systematically thicker and the water depths are shallower. We suggest that two end‐members of oceanic crust exist in fast spreading environments: one thick, underlain by a clear Moho; the other thinner, without a Moho; with all intermediate situations. In the Oman ophiolite, the best‐preserved on‐land analogue of fossil oceanic lithosphere created by fast‐spreading, the boundary between the mantle peridotites and the lower crustal gabbros mainly consists of a dunitic transition zone (DTZ) ranging from a few meters to a few hundred meters in thickness. A sudden influx of seawater down to the base of the crust at the mid‐ocean ridge (MOR) results in the hydrous (re‐)melting of mantle peridotites, producing a dunitic residue at the crust–mantle boundary that represents the most reflective Moho. At the same time, the hydrous melting, in addition to the normal decompression melting, beneath the MOR, increases the thickness of the oceanic crust by enhancing magma production. In the absence of hydrous melting, the DTZ is thin or absent at the crust–mantle boundary, and instead the uppermost mantle harzburgite is intruded by gabbros, and/or the overlying crustal gabbro is intruded by numerous wehrlite bodies, which will be seismically gradational.